Online Buying and Selling Application of Sacrificial Animals Using Scrum Method During the Covid-19 Pandemic - Endra Rahmawati (Fakultas Teknik Universitas Bhayangkara, 2022)
Since the pandemic entered Indonesia, many people have switched to the online buying and selling transaction process.The Covid-19 pandemic has had a very significant impact on the transaction process which was previously carriedout traditionally, especially for the sale and purchase of sacrificial animals. The process of selling sacrificial animalsis still done traditionally by ordering directly by phone and coming directly to the cattle pen for the sacrificial animalsdesired by consumers. To deal with these problems, an alternative solution is needed that can create a informationsystem solution as a medium for selling livestock online. This online sacrificial animals buying and selling applicationwill be developed using the SCRUM method. When conditions change like this during the Covid-19 pandemic, SCRUMis suitable for developing applications. This is because Scrum is an iterative method that is included in the Agilemethod in how to manage and run an application development project. The features or menus that will be built in thisapplication including Master Data Management, and get Reports on all Transactions periodically, Shipping / DeliveryTransactions, notifications for Animal Husbandry Services. However, due to the conditions of the Covid-19 pandemic,there are several features that will be added, namely the Results of Routine Examination of the Condition of SacrificialAnimals for the last 1 month which will continue to be updated by livestock owners, and Description of PhysicalCondition of Sacrificial Animals which includes Species, Skin Color, Weight (Kg ), Height (cm). The results of theBlack Box Testing show that all functions have run well with a percentage of successful functional running of 97.3%.Keywords: Application, Online Buying and Selling, Sacrificial Animals, Scrum Method.